VARIASI GELOMBANG, ARUS PERMUKAAN, DAN ANGIN DI LAUT HALMAHERA BAGIAN BARAT - I Dero, Arfisda; M Abdullah, Rommy; Alin Nuary, Zaky (Jurnal Widya Climago, 2022)
The Halmahera Sea has a mass of water which is influenced by the dynamics of the atmosphere-ocean of the Pacific Ocean. The existence of a system of equatorial currents and warm pools has a major influence. Conditions of waves, currents and wind greatly affect the activities of the people around these waters. This research is expected to be able to provide initial information for the community in carrying out their daily activities. The data used is remote sensing data from satellite images of waves, surface currents, and surface winds. The data is processed seasonally using spatio-temporal analysis and linear regression analysis. The results showed that the spatial pattern of wave height, surface currents, and surface winds that occurred in the western part of the Halmahera Sea showed a seasonal pattern which was influenced by monsoon winds. In this study, it was shown that there is an influence between wind speed on wave formation and surface currents in the western Halmahera Sea.